PATRIOTIC UPBRINGING OF STUDENT YOUTH IN THE CONTEXT OF THE PROGRAMME "RUKHANI ZHANGYRU" - Aysina, S.T.; Brimzhanova, K.S.; Ivanova, E.N. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article discusses the issue of formation of Patriotic education of student youth in the framework of realization of special projects of the programme "Rukhani zhangyru".
Keywords: education; formation; patriotism; value; modernization; unity; potential